(untitled) (LEARNing Landscapes, 2012)
In this interview, eminent psychologist Jerome Bruner takes us back to the 1960s to trace the beginning of his interest in educational theory. He describes the circumstances that led to writing his seminal book, "The Process of Education," and his surprise at how well the book was received worldwide, both from the public and academics. Dr. Bruner believes that "the easiest and most natural way we organize things is in a story-telling mode." This interview is a good example of his belief as he relates stories of the launching of Sputnik, the famous meeting at Woods Hall, his childhood friends, and his academic career. Finally, he invites us to "go beyond" as he explains his view of the future of education.